The forge of vision a visual history of modern Christianity - Morgan, David 1957- (University of California Press, 2015)
"Religions teach their adherents how to see and feel at the same time, so learning to see is not a disembodied process but one hammered out on the forge of human need, social relations, and material practice. Therefore, religions may be studied through the lens of salient visual themes. This book tells a history of Catholic and Protestant Christianity since the sixteenth century by selecting visual themes that have shaped the development of the religion throughout the modern era. Chapters examine a variety of visual practices, including imagination, envisioning nationhood, the likeness of Jesus, modern art as a spiritual quest, the material life of words, and the importance of images for education, devotion, worship, and domestic life."--Provided by publisher